PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN SUSAN LOUCKS-HORSLEY PADA MATERI GETARAN, GELOMBANG DAN BUNYI KELAS VIII DI SMP - Rifda Yana Zubair; Syahril Syahril; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study was aimed to develop learning tools based on the Susan Loucks-Horsley Model on Vibration and wave material for class VIII in junior high school, to investigate the validity of learning devices that have been developed. The device development model used is the Research and Development (R & D) model with a design 4D developed by S. Thiagarajan, et al. Teaching tools developed in the form of lesson plans (RPP), student worksheets (LKPD), and learning outcomes tests arranged based on indicators of students' science process skills. Data collection using sheets assessment of the validation of learning tools for assessing lesson plans, student worksheet, and learning outcomes tests that are used by the validator to assess learning tools. Data analysis was carried out by descriptive analysis. The results showed that the validity data obtained for the average validity of the lesson plan was 3.39 with a very high category, the average validity of LKPD was 3.17 with a very high category, and the average learning outcome test was 3.30 with the category Very high. It can be concluded that the learning device developed based on the Susan Lewis-hosley model is declared valid and can be used as a learning device for class VIII vibrations and waves in junior high schools to be tested for its feasibility. Key Words: Learning Tools, Susan Loucks-Horsley Model, Science process skills